Glutamine: A potentially useful supplement for athletes - Antonio, J.; Street, Ch. (Canadian Journal of Applied Physiology, 1999)
This brief review will describe a number of studies on the effects of glutamine supplementation on muscle protein mass, immune system function, and glucose regulation. Based on the available clinical evidence, we would speculate that glutamine has potential utility as a dietary supplement for athletes engaged in heavy exercise training.